Contribution of Motor Educability, Coordination, and Confidence to the Ability to Perform Flic-Flac Artistic Gymnastics Extracurricular at SDN Kayen I Bandarkedungmulyo, Jombang - Purwanto, Hadi; Pratama, Budiman Agung; Atrup, Atrup (UNIVERSITAS NEGERI MAKASSAR, 2021)
This research is based on the observations and experiences of researchers, that not all elementary schools in the district know or do gymnastics in general, specifically artistic gymnastics. The problems in this problem are: 1) How big is the contribution of Motor Educability to the ability to do the flic-flac movement? 2) How big is Eye-Hand-Foot Coordination to the ability to do the flic-flac movement? 3) How much do you contribute and are confident in doing the flic-flac movement? 4) Is there a joint contribution of motor educability, coordination, and self-confidence to the ability to perform flic-flac movements? 5) Among the contributions of motor educability, coordination, and self-confidence, which one has the biggest role in the ability to perform artistic gymnastics flic-flac movements? Scientific work, as material to be studied, by further researchers. The type of research used in this study is a quantitative research study whose data is in the form of numbers. Using independent and dependent variables. Instruments that have been tested for validity and reliability. Based on the results that have been obtained, it shows that the contribution of motor educability, coordination, and self-confidence, the ability to perform flic-flac movements of students will increase. A teacher can explain motor educability clearly so that students can understand it. The ability to perform the student's flic-flac movement will decrease if the student's eye-hand and foot coordination are not balanced so that it can be at risk of causing injury. The maturity level of motor educability and self-confidence is high, it will be easier for you to do the flic-flac movement. The lower eye-hand-foot coordination will affect increasing the possibility of injury to students. Based on the conclusions of the research, it is suggested that there is a relationship between the contribution of motor educability, coordination, and self-confidence to the ability to perform extracurricular artistic gymnastics flic-flac at SDN Kayen I Bandarkedungmulyo, Jombang.